2016
DOI: 10.1186/s40695-016-0017-z
|View full text |Cite
|
Sign up to set email alerts
|

Chronic vulvar pain in a cohort of post-menopausal women: Atrophy or Vulvodynia?

Abstract: BackgroundAlthough postmenopausal vulvar pain is frequently attributed to vaginal atrophy, such symptoms may be due to vulvodynia, a chronic vulvar pain condition. Given the limited research on vulvodynia in postmenopausal women, the objective of this study was to provide preliminary population-based data on the associations of vaginal symptoms, serum hormone levels and hormone use with chronic vulvar pain in a multiethnic sample of post-menopausal women.MethodsWe used data from 371 participants at the Michiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“… 10 , 11 There is a second peak of vulvar pain around menopause, in part due to vulvovaginal atrophy but also new-onset or recurrent vulvodynia. 12 Vulvodynia can occur in childhood, but studies are sparse, and in many cases, persistent pain is found to have an underlying cause. 11 …”
Section: Prevalencementioning
confidence: 99%
“… 10 , 11 There is a second peak of vulvar pain around menopause, in part due to vulvovaginal atrophy but also new-onset or recurrent vulvodynia. 12 Vulvodynia can occur in childhood, but studies are sparse, and in many cases, persistent pain is found to have an underlying cause. 11 …”
Section: Prevalencementioning
confidence: 99%
“…Buscando solucionar parte dessas questões, é importante que o médico se atente à precisão ao diagnosticar infecções vaginais ou vaginites atróficas, apontados no nosso estudo como os diagnósticos mais frequentemente deferidos à paciente com sintomas de VVD. Muitas vezes o o quadro sintomatológico de vaginite atrófica se confunde com o da vulvodínia devido a alguns sintomas que podem ser comuns a ambas, tais como ardência vulvar, dispareunia, presença de fissuras no introito vaginal, diminuição da lubrificação vaginal (113) . Nossos resultados apontaram que a maior parte das mulheres diagnosticadas pelo nosso estudo com vulvodínia, que reportaram tratamento prévio com estrogênio tópico reportaram nenhum ou somente discreto alívio da dor vulvar.…”
Section: Discussão Geralunclassified